Leadership Style And Employee Productivity In Manufacturing Companies In Indonesia - Suprayitno, Degdo (Commercium : Journal of Business and Management, 2024)
This study uses a quantitative approach to investigate the complex relationships between employee productivity and leadership styles in Indonesian manufacturing firms. After 150 participants' data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), important findings were found. Employee productivity was greatly impacted by the emergence of transformational leadership as the prevailing approach. Positive relationships highlighting the significance of structured rewards were also shown by transactional leadership. Conversely, there was a detrimental impact on production from laissez-faire leadership. According to the findings, increased productivity in Indonesia's manufacturing sector can be achieved by matching leadership tactics with organizational and cultural circumstances.